2020
DOI: 10.3390/ijerph17196958
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Rater Test-Retest Reliability of a Modified Child Functioning Module, Self-Report Version

Abstract: Determining disability prevalence is a growing area for population statistics, especially among young adolescents. The Washington Group on Disability Statistics is one source of reporting disabilities through functional difficulties. Yet, young adolescents self-reporting through this measure is in its infancy. The purpose of this study was to carry out an intra-rater test-retest reliability study on a modified set of items for self-reporting functional difficulties. Young adolescents (N = 74; boys = 64%; age M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Age categories were created based on the nearest whole year for 16y, 17y, 18y olds. Disabilities were calculated through the self-reported version of the child functioning module of the Washington group on disability studies [ 23 ]. There are 11 items with a four-point scale on core functions for adolescents namely, seeing, hearing, speaking, walking, concentrating, learning, self-care, remembering, change of routines, getting friends, controlling own behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Age categories were created based on the nearest whole year for 16y, 17y, 18y olds. Disabilities were calculated through the self-reported version of the child functioning module of the Washington group on disability studies [ 23 ]. There are 11 items with a four-point scale on core functions for adolescents namely, seeing, hearing, speaking, walking, concentrating, learning, self-care, remembering, change of routines, getting friends, controlling own behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming a correlation coe cient of 0.99, andαandβvalues of 0.05 and 0.10 for type I and II errors, respectively, the minimal sample size required to achieve the desired statistical power (0.80) was n=5. A total of 30 urological medical staffs were included in this study to evaluate the consistency of hematuria colorimetric card, including 10 urologists, 10 urological nurses and 10 medical students who practice in urology [7]. All people are screened by the Color Blind Examination Chart, and none of them was color blind and weak.…”
Section: Methodsmentioning
confidence: 99%
“…The question sets have undergone cognitive and field testing in different settings. Additionally studies of the CFM have found good internaland factor-level consistency and substantial or moderate inter-rater and test-retest reliability, although similar studies for the WG-ES are lacking [23,24].…”
Section: Case Definition and Data Collectionmentioning
confidence: 99%